Penilaian Risiko Pelayanan Bongkar Muat Kapal Di Pelabuhan Lembar PT. ASDP Indonesia Ferry (Persero) Cabang Lembar - Ahmad Jupri; Yulianti Yulianti; Supardiono Supardiono; Pahmi Husaini; Hilman Ahyadi; Lilik Hidayati (Universitas Mataram, 2026)
Risk assessment is a planned approach to identify potential threats, assess their likelihood of occurrence, and measure their potential impacts, with the aim of determining effective control measures to minimize losses to individuals, resources, the environment, and the organization's image. The purpose of this study is to determine the risks that occur in ship service operations and loading and unloading of goods at Lembar Port. This study was conducted in July-August at Lembar Port, West Lombok, using a descriptive qualitative approach. The research method includes data collection through field observations, interviews with officers, and documentation studies. The risk assessment process was carried out by identifying risky events at the ship berthing stage, the loading and unloading process, until the ship leaves the dock. Risks found include ship collisions, damaged dock facilities, truck rolling, lack of supervision, ship running aground, leaking ships, falling cargo, delays in loading and unloading, and fires during refueling. The results of the risk matrix analysis show that most risks are in the low to medium category, but there are several high-level risks such as delays in loading and unloading, work inefficiencies, worker accidents, and fires during refueling. To reduce the impact of these risks, it is necessary to implement mitigation in the form of the use of personal protective equipment (PPE), routine K3 training, improvements to standard operating procedures (SOPs), increased supervision, and the use of technology in operational planning and control.